2002
DOI: 10.1021/jm025530f
|View full text |Cite
|
Sign up to set email alerts
|

Arylsulfonamidothiazoles as a New Class of Potential Antidiabetic Drugs. Discovery of Potent and Selective Inhibitors of the 11β-Hydroxysteroid Dehydrogenase Type 1

Abstract: Novel antidiabetic arylsulfonamidothiazoles are presented that exert action through selective inhibition of the 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1) enzyme, thereby attenuating hepatic gluconeogenesis. The diethylamide derivative 2a was shown to potently inhibit human 11beta-HSD1 (IC(50) = 52 nM), whereas the N-methylpiperazinamide analogue 2b only inhibited murine 11beta-HSD1 (IC(50) = 96 nM). Both compounds showed >200-fold selectivity over human and murine 11beta-HSD2. 2b was subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
145
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 11 publications
(24 reference statements)
6
145
0
3
Order By: Relevance
“…Discussion 11b-HSD1 is a tissue-specific prereceptor regulator of the GC responses (Tomlinson et al 2004). Its importance as a possible therapeutic target in the management of human obesity and insulin resistance is supported by the development of selective 11b-HSD1 inhibitors that improve glucose tolerance in diabetic mice (Alberts et al 2002, Barf et al 2002. In the human eye, the isozyme has been implicated in the pathogenesis of ocular surface disease and glaucoma, the leading causes of worldwide blindness (Stokes et al 2000, Rauz et al 2003a.…”
Section: Western Blot Analysesmentioning
confidence: 99%
“…Discussion 11b-HSD1 is a tissue-specific prereceptor regulator of the GC responses (Tomlinson et al 2004). Its importance as a possible therapeutic target in the management of human obesity and insulin resistance is supported by the development of selective 11b-HSD1 inhibitors that improve glucose tolerance in diabetic mice (Alberts et al 2002, Barf et al 2002. In the human eye, the isozyme has been implicated in the pathogenesis of ocular surface disease and glaucoma, the leading causes of worldwide blindness (Stokes et al 2000, Rauz et al 2003a.…”
Section: Western Blot Analysesmentioning
confidence: 99%
“…Selective inhibitors of human 11β-HSD1 have already been synthesised [80]. These drugs could lower intrahepatic and intra-adipose tissue cortisol concentrations and thereby regionally enhance insulin sensitivity, reduce gluconeogenesis and potentially even adiposity.…”
Section: Studies With 11β-hsd Inhibitorsmentioning
confidence: 99%
“…Because adipose 11␤-HSD1 activity positively correlates to body mass index, percentage of body fat, and waist circumference as well as fasting glucose, insulin levels, and insulin resistance (23)(24)(25), 11␤-HSD1 is currently considered a promising pharmaceutical target for the treatment of diabetes type 2. Indeed, recent animal studies showed that the administration of a selective 11␤-HSD1 inhibitor to diabetic mice reduced blood glucose levels and increased insulin sensitivity (26,27). In addition to its role in the activation of glucocorticoids, 11␤-HSD1 might play a role in the detoxification of reactive ketocompounds such as the potent tobacco carcinogen nicotinederived nitrosamine ketone (NNK) and the anti-cancer drug oracin (28,29).…”
mentioning
confidence: 99%